HUBUNGAN TERAPI RELAKSASI BENSON TERHADAP DISMENOREA PRIMER PADA REMAJA PUTRI DI UPTD PUSKESMAS TARAMAN: HUBUNGAN TERAPI RELAKSASI BENSON TERHADAP DISMENOREA PRIMER PADA REMAJA PUTRI DI UPTD PUSKESMAS TARAMAN - Ade Marlisa Rahmadayanti; Istiqomah Febrianty; Nyoman Jesika (CV. Cendikiawan Muda Sriwijaya, 2026)
Symptoms of dysmenorrhoea that are often experienced by young women during menstruation include spasms or stiffness in the lower abdominal area, because the feeling of discomfort can disrupt activities and impact the quality of life, including depression and decreased concentration. These symptoms can occur before and during menstruation, usually 1 day before and 1-2 days during menstruation. Pharmacological treatment is done by using non-steroidal anti-inflammatory drugs (NSAIDs), while non-pharmacological pain treatment can be done by deep breathing relaxation or Benson relaxation which can control pain. This research uses a pre-experimental method with a quasi-experimental approach and a pre and posttest one group design research design. The sample in this study was 15 young women who experienced primary dysmenorrhoea in the UPTD work area of ​​the Taraman Community Health Center. The results of the study showed that the average dysmenorrhoea experienced by young women before and after the intervention (Benson Relaxation Therapy) was moderate pain (4.60) at the pretest, while after the posttest the respondents' average pain was mild pain (3.13). The difference in the average interval before and after intervention was (1.47). Through the Wilcoxon test, p-value = 0.000 (α < 0.05). So it was concluded that there was a relationship between Benson relaxation therapy and reducing the pain scale of primary dysmenorrhoea in young women at the UPTD Taraman Health Center.